The basic science of cystic fibrosis. Issue 4 (April 2015) - Bowen, Sarah-Jane; Hull, Jeremy
Abstract: Cystic fibrosis (CF) is a monogenic autosomal recessive condition affecting approximately 1 in 3000 in the Caucasian population. It is a life-limiting condition with effects on multiple organs, predominantly the lungs, gastrointestinal tract, pancreas and liver. The cystic fibrosis transmembrane conductance regulator (CFTR) anion channel regulates chloride, bicarbonate and sodium transport across cell membranes, predominantly in epithelial tissues. In cystic fibrosis the CFTR protein is structurally or functionally abnormal due to mutations in the CFTR gene located on Chromosome 7. Approaching 2000 CFTR mutations have been identified to date though not all are disease-causing. There is phenotypic heterogeneity in CF due to variability in how mutations affect CFTR biosynthesis and the impact of genetic and environmental modifying factors. Advances in understanding of the pathophysiology of CF have led to improved outcomes though there remains a significant burden of disease. There have been promising results from the development of mutation-specific small molecule therapies and personalised care is felt to be crucial in further improving the outlook for those with CF.